(3HZjI GdCQjH aj hUGd GdMHjHs - (3GdchGRj, eMehO Hf EHQGgje Hf Wgs ((3YHO Gddg Hf YjSi Hf ESeGYjds)
(3ChdgG (B:s
(3bGd GdeLJGM GdeMJGL(B... (3GdMeO ddg GdPj QaY ebGeGJ GdYTGb(B... (3CeG HYO, aEfj deG JQGceJ Ydj Gdgehe(B... (3Yf dj EfTGA ebGeI JSdjfj aj GdSaQ hGdEbGeI(B...s
(3BNQgG (B:s
(3gPG BNQ GdebGeGJ GdJj CfTCJgG HjO GdJbUjQ, hCedjJgG HdSGf GdJbJjQ(B...(3hGdMeO ddg QH GdYGdejfs
(3JHUQI GdYfhGf (B:s
(3ebGeI GdchGRjs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdCOHs